Lowering fecal immunochemical test positivity threshold vs multitarget stool RNA testing for colorectal cancer screening - Niedermaier, Tobias; Seum, Teresa; Hoffmeister, Michael; Brenner, Hermann (The journal of the American Medical Association, 2004)
Fecal immunochemical tests (FITs) for hemoglobin are the most widely used screening tests for colorectal cancer (CRC) globally. However, they have limited sensitivity in detecting early-stage CRC and CRC precursors. In 2023, the CRC-PREVENT study, a blinded, prospective, cross-sectional study that enrolled the target population for CRC screening, demonstrated increased sensitivity for CRC of a multitarget stool RNA (mt-sRNA) test compared with FIT alone (94% vs 78%). The mt-sRNA test incorporated a commercially available FIT (iFOBT OC-Auto; positivity threshold, 20 μg hemoglobin per gram of feces), concentration of 8 RNA transcripts, and participant-reported smoking status. However, this increase in sensitivity came at a substantial loss of specificity for no lesions compared with FIT alone (88% vs 96%). This analysis evaluated whether comparable levels of sensitivity and specificity could be achieved by lowering the FIT positivity threshold, without additional stool RNA testing and smoking assessment.